The influence of a carbohydrate beverage on endurance capacity and tennis hitting performance following a simulated tennis match - McCarthy, P. R.; Thorpe, R.; Williams, C.
Tennis matches can last from 1 to 5 hours. Throughout this time period players need to be able to maintain technique and concentration, coupled with the ability to react and move rapidly around the court. Fatigue from maximal tennis hitting has been observed to result in a decline in hitting accuracy (McCarthy et al. 1995). The primary causes of fatigue under such conditions are suggested to be the decline in the body's carbohydrate reserves. Limited research exists on the influence of carbohydrate ingestion on simulated 'actual matchplay'. The present study investigated the influence of ingesting 3ml.kg-1BM of either a 6.9% carbohydrate-electrolyte (CHO-E) beverage or a flavoured water placebo (P) upon endurance capacity and tennis hitting performance following a simulated tennis match. In order to simulate the tennis performance test as closely as possible to 'actual matchplay', video analyses of 7 professional tennis matches were performed. Descriptive statistics reveal a mean rally time of 2.9 ± 0.1s (Mean ± S.E.M.), mean recovery between points and games of 19.4 ± 0.3s and 81.1 ± 4.7s and mean game and match lengths of 191.4 ± 8.5 min and 67.7 ± 21.3 min respectively. Initially, ten elite tennis players (5 male, 5 female) performed a 4 min on court warm up against a ball machine (15 balls per minute) and a one minute service warm up to both service courts on a Matchplay?, En-Tout-Cas? surface. Nude body mass (kg) was obtained pre- and post-trial. Each main trial was split into two parts, A and B. Subjects were requested to hit maximally throughout both trials against a random feed ball machine (30 balls per min). In part A the match analysis statistics were utilised to create simulated 'actual matchplay'. Players performed a service game (SG) consisting of repeated sets of a 4s service, an 8s groundstroke hit and a 20s recovery, for the duration of 3min 16s. A long recovery period (LR) of 1 min 30s proceeded the service game. A simulated receiving game (RG) was subsequently performed consisting of repeated sets of a 10s groundstroke hit and a 20s recovery period for the duration of 3 min 10s, followed immediately by a 30s short recovery period (SR). The set of SG + LR + RG + SR was continued for 92 min 46s (Part A). Part B was a continuous performance test (PT), performed immediately after Part A, requiring subjects to aim their returns towards either of two targets placed in the rear corners of the singles court. Part B was continued to the point of 'volitional exhaustion' or when the required hitting frequency for two consecutive ball feeds could no longer be maintained. The player's skilled performance was assessed by the number of returns landing in the rear singles court area, excluding the target (Consistency score), landing on either of the two targets (Accuracy score) or hit in the net or any other area other than the aforementioned (Out score) respectively. Percentage scores over each minute of the PT were calculated, whereby 'consistency' plus 'accuracy' plus 'out' equalled 100%. Grip strength and endurance were measured by a Jamar? grip dynamometer pre-Part A, pre-Part B and post-Part B. Capillary blood samples were obtained from the thumb and were analysed for blood glucose and blood lactate concentrations respectively. A double-blind random cross-over design was used with a one week interval between trials. The prescribed fluid intake was administered post warm-up, at alternating LR periods and at the end of Part A. A paired t-test (one tail) was used to determine the differences between the CHO-E and P trials in the mean time to exhaustion, changes in body mass and heart rates in the SG and RG respectively. A two way analysis of variance (ANOVA) for repeated measures was used to determine the differences between conditions in all other physiological parameters and skill over the PT (start, 25%, 50%, 75% way through PT and at exhaustion). Post-hoc Tukey tests established the location of the differences.